Dilute Aqueous-Aprotic Electrolyte Towards Robust Zn-Ion Hybrid Supercapacitor with High Operation Voltage and Long Lifespan - Wu, Shuilin; Yang, Yibing; Sun, Mingzi; Zhang, Tian; Huang, Shaozhuan; Zhang, Daohong; Huang, Bolong; Wang, Pengfei; Zhang, Wenjun (Nano-Micro Letters, 2024)
With the merits of the high energy density of batteries and power density of supercapacitors, the aqueous Zn-ion hybrid supercapacitors emerge as a promising candidate for applications where both rapid energy delivery and moderate energy storage are required. However, the narrow electrochemical window of aqueous electrolytes induces severe side reactions on the Zn metal anode and shortens its lifespan. It also limits the operation voltage and energy density of the Zn-ion hybrid supercapacitors. Using ‘water in salt’ electrolytes can effectively broaden their electrochemical windows, but this is at the expense of high cost, low ionic conductivity, and narrow temperature compatibility, compromising the electrochemical performance of the Zn-ion hybrid supercapacitors. Thus, designing a new electrolyte to balance these factors towards high-performance Zn-ion hybrid supercapacitors is urgent and necessary. We developed a dilute water/acetonitrile electrolyte (0.5 m Zn(CF3SO3)2 + 1 m LiTFSI-H2O/AN) for Zn-ion hybrid supercapacitors, which simultaneously exhibited expanded electrochemical window, decent ionic conductivity, and broad temperature compatibility. In this electrolyte, the hydration shells and hydrogen bonds are significantly modulated by the acetonitrile and TFSI− anions. As a result, a Zn-ion hybrid supercapacitor with such an electrolyte demonstrates a high operating voltage up to 2.2 V and long lifespan beyond 120,000 cycles. Highlights: 1 A novel aqueous/aprotic electrolyte with low salt concentration (i.e., 0.5 m Zn(CF3SO3)2+1 m LiTFSI) demonstrated an expanded electrochemical window, which can simultaneously stabilize Zn metal anode and increase the operation voltage of Zn-ion hybrid supercapacitors. 2 The coordination shell of the electrolyte induced by acetonitrile and LiTFSI can not only suppress the Zn corrosion and hydrogen evolution reaction but also promote the cathodic stability and ion migration, which is depicted by the density functional theory simulations together with experimental characterizations. 3 The Zn-ion hybrid supercapacitor based on the developed electrolyte can operate within 0–2.2 V in a wide temperature range with an ultra-long lifespan (> 120,000 cycles).